Impregnation of different coals and biomass with rapeseed oil for intensifying their ignition in a heated air stream during oil-free boiler start-up; Fuel Processing Technology; Vol. 236 - Feoktistov D. V. Dmitriy Vladimirovich; Glushkov D. O. Dmitry Olegovich; Nurpeiis А. Е. Atlant Ediluly; Orlova E. G. Evgeniya Georgievna; Samoylo A. S. Aleksandr Sergeevich; Zhizhaev A. M. Anatoly Mikhaylovich; Zhuykov A. V. Andrey Vladimirovich (2022, 2022)
Title screen